Secondary caries prevention by considering the features of enamel prisms location during filling of carious cavity - Gurtova, Ja. M.; Schneider, S. A.; Breus, V. E.; Ulianov, V. O. (Journal of Education, Health and Sport, 2019)
Enamel is the hardest substance in the human body and contains the highest percentage of minerals (96%), with water and organic material composing the rest. The objective: to improve the quality of carious dental cavities filling in patients by determining the regularities of enamel prisms direction and quality of “enamel-filling”connection in topographically different parts of permanent human canines crown. Materials and methods. 40 permamnnet canines with intact enamel, removed because of trauma or orthodontic indications; 89 caries patients. Results. Angulation and direction of enamel prisms in different parts, surfaces and layers of a human permanent canines has been revealed. Conclusions. Features of different parts of enamel prisms inclination in toporgathically different parts of a human permanent canines has been shown. It has been revealed that the efficiency of a filling and enamel coalescence depends on the prevailing direction of enamel prisms in different parts of canine crown. Taking into account the peculiarities of enamel prisms location in the tooth crown at carious cavity preparation, increases the effectiveness of secondary caries prevention.